Efecto antioxidante del aceite esencial de tipo (minthostachys mollis.) en el aceite de Aguacate (persea americana). - Chilig Paneluisa, Soraya Paulina (2018)
The present investigation carried out a study about the antioxidant activity of the essential oil of Type (Minthostachys mollis) to take advantage of the characteristics of this plant in the avocado oil (Persea americana) since the artificial antioxidants are widely used in the food industry, not however, research is currently being carried out on natural antioxidants, which is a worldwide trend in consumer favoritism. Variables were applied as different amounts of Type oil (0.04%, 0.06%, 0.08%), this being Factor A and different storage container (amber and colorless) as Factor B. During the investigative process that was carried out during the period of 9 days, after one day the oils were analyzed by chemical physical study methods such as peroxide index (IP), acidity (% AGL), refractive index (IR), pH and organoleptics such as color and odor for which it was used scales of different positive and negative attributes. A randomized complete block design (A * B) + 1 (control) was applied, which were analyzed in the INFOSTAT (IS) statistical program. Therefore, T4 (a2b2) was determined as the best treatment with respect to the rest of the treatments, comparing it with the control to which a synthetic antioxidant called Butyl hydroxytoluene (BHT) plus amber container was added. Where it was shown as the optimum amount of 0.06% Type Oil and the appropriate amber colored container, which retained the physical and chemical characteristics of the oil under study, the results were IP (5.0165 milli equivalents of oxygen active / kg), acidity (0.5653% free fatty acids), IR (1.4695) and pH (6.3460) of T4 that according to the standard NMX-F-052-SCFI-2008. OILS AND GREASES-AVOCADO OIL SPECIFICATIONS FATS AND OILS-AVOCADO OIL-SPECIFICATIONS comply with the parameters, with respect to the smell during the investigation the treatments with more essential oil kept their mint smell while the others decreased their odor dried fruits, in the color it was observed that the color tendency predominated between yellowish green and yellow greenish.